2000
DOI: 10.1023/a:1004157915077
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: It has been suggested that the karyotype of the marsupials derived from a low diploid number (2n = 14) which originated, through fissions of biarmed chromosomes, the karyotypes with a higher 2n. The telomeric sequence (T2AG3)n was in situ hybridized to the chromosomes of Gracilinanus microtarsus and G. emiliae, Micoureus demerarae and Marmosa murina, species with 2n = 14, in Monodelphis sp., M. domestica, M. kunsi and M. brevicaudata with 2n = 18, and in Lutreolina crassicaudata, Didelphis albiventris, Chirone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…The finding of interstitial telomeric sequences (ITS) in the autosomes of Didelphidae species with 2n = 14 and 2n = 18, but not in those with 2n = 22, led to the suggestion that the karyotype of South American marsupials would have proceeded through centric fusions leading to the reduction in diploid number from an ancestral complement with at least 22 chromosomes (Svartman and Vianna-Morgante, 1998; Carvalho and Mattevi, 2000). This hypothesis defied the idea of the “ancestral” 2n = 14 marsupial karyotype which had prevailed for the previous three decades.…”
Section: Karyotype Evolution In Marsupialsmentioning
confidence: 99%
See 2 more Smart Citations
“…The finding of interstitial telomeric sequences (ITS) in the autosomes of Didelphidae species with 2n = 14 and 2n = 18, but not in those with 2n = 22, led to the suggestion that the karyotype of South American marsupials would have proceeded through centric fusions leading to the reduction in diploid number from an ancestral complement with at least 22 chromosomes (Svartman and Vianna-Morgante, 1998; Carvalho and Mattevi, 2000). This hypothesis defied the idea of the “ancestral” 2n = 14 marsupial karyotype which had prevailed for the previous three decades.…”
Section: Karyotype Evolution In Marsupialsmentioning
confidence: 99%
“…The results in the eight 2n = 14 species analyzed were more variable: four species had no ITS ( Caluromys philander , Metachirus nudicaudatus ; Marmosa murina and Gracilinanus emiliae ), Gracilinanus microtarsus had ITS on pair 1, Micoureus demerarae had a maximum of eight signals on the four largest autosome pairs, Marmosops incanus had ITS on pairs 1-5 and M . parvidens presented ITS in all of its six autosomal pairs (Svartman and Vianna-Morgante, 1998; Carvalho and Mattevi, 2000; Pagnozzi et al , 2000, 2002). …”
Section: Karyotype Evolution In Marsupialsmentioning
confidence: 99%
See 1 more Smart Citation
“…If the marsupial ancestor had a 2n = 22 chromosome complement, it would probably resemble karyotypes of members of Family Didelphidae with 22 chromosomes, since the American marsupials are at the base of the marsupial phylogenetic tree [13,18]. The strongest evidence for the higher ancestral number is the presence of interstitial telomere signals in members of Didelphidae with 2n = 18 or 2n = 14 karyotypes, suggesting that lower diploid number karyotypes were derived by chromosome fusions, ultimately leading to the 2n = 14 karyotype commonly found amongst marsupials, and recognised as the basal karyotype of Australidelphia [12,19]. However, Pagnozzi et al [20,21] observed that these interstitial signals coincide with constitutive heterochromatin, and proposed that they actually represent satellite DNA rather than telomeric sequence, as was also concluded for an Australian species with a 2n = 14 karyotype [22].…”
Section: Introductionmentioning
confidence: 99%
“…Cross-species chromosome painting demonstrated that, despite the commonality of the 2 n  = 22 diploid number across different marsupial families, the 18 autosomal segments detected were arranged differently between 2n = 22 species (O’Neill et al 1999; Rens et al 2003). The main evidence to support the 2 n  = 22 hypothesis was the observation of interstitial telomere signals in members of the Family Didelphidae, a family representing one of the earliest offshoots of the marsupial lineage, with 2 n  = 14 or 2 n  = 18 karyotypes, suggesting that chromosome fusions were responsible for these lower diploid numbers (Carvalho and Mattevi 2000; Svartman and Vianna-Morgante 1998). The inability to compare marsupial chromosome arrangement to outgroup species using chromosome painting prevented further testing of either hypothesis.…”
Section: Mammalian Ancestral Karyotype Reconstructionsmentioning
confidence: 99%